Maternal and fetal outcome in primigravida with unengaged head at term in labour - L., Reshma; Sujatha Prabhu,; Kusuma Naik M. V., (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Unengaged head in a primigravida at term gestation at the onset of labor is considered as an obstetric risk factor for dysfunctional labor. Careful monitoring of the progress of labor and timely medical intervention reduced the risk of dysfunctional labor and Cesarean delivery. This study was to assess the effect of unengaged head on course of labor, duration of labor, its maternal and fetal outcome in primigravida at term in labor. Methods: This prospective cross-sectional study was conducted in 100 primigravida with term gestation, unengaged head with spontaneous onset of labor meeting the inclusion criteria admitted to labor ward, Department of Obstetrics & Gynecology, ESIC-MC & PGIMSR Hospital, Bengaluru during January 2019 to June 2020. After detailed clinical evaluation, labor monitored partographically and CTG for fetal surveillance and when necessary, interventions like augmentation of labor and operative vaginal or cesarean delivery performed. Results: Among 100 primigravidae, 19% had floating head, 53% at -3 and 28% at -2 station at the time of onset of labor. The mean duration of 1st, 2nd stage and total duration of labor was higher in freely floating head compared to -3 and -2 station. The need for augmentation of labor was 100% with freely floating head than with -3 and -2 station. 77% delivered vaginally and 23% by LSCS, arrest disorders being the main indication. There was no significant difference in maternal morbidity or APGAR score at 5 min. 88% of the babies delivered with good APGAR and 12% required NICU admission Conclusions: Our study demonstrates that higher the fetal head station at the onset of labor, greater the duration of labor and the need for augmentation. Unengaged head per se is not an indication for LSCS as 77% of them delivered vaginally with partographically monitored labor.